2021
DOI: 10.4162/nrp.2021.15.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Gender and age group differences in nutrition intake and dietary quality of Korean adults eating alone: based on Korean National Health and Nutrition Examination Survey Data, 2013–2016

Abstract: BACKGROUND/OBJECTIVES This study investigated gender and age differences in nutrient intake and dietary quality of people eating alone. SUBJECTS/METHODS From Korean National Health and Nutrition Examination Survey 2013–2016 data, 2,305 adults aged 20 years and older that ate meals alone were included in this study. Their energy and nutrients intakes, as well as their nutrient adequacy ratio (NAR), mean adequacy ratio (MAR), and index of nutritional quality (INQ) were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
6
9
0
Order By: Relevance
“…However, in females, the total energy intake (carbohydrate, fat, and protein) was significantly different between the MetS and non-MetS groups. This result is supported by a previous study, which reported that the dietary quality and food diversity of females was better than that of males (44). Moreover, the overall low nutrient intake and low nutrient density of meals were the major nutritional problems in the group of ESH.…”
Section: Discussionsupporting
confidence: 83%
“…However, in females, the total energy intake (carbohydrate, fat, and protein) was significantly different between the MetS and non-MetS groups. This result is supported by a previous study, which reported that the dietary quality and food diversity of females was better than that of males (44). Moreover, the overall low nutrient intake and low nutrient density of meals were the major nutritional problems in the group of ESH.…”
Section: Discussionsupporting
confidence: 83%
“…Other studies reported that the greater the number of solo meals, the higher the rate of depression. Notably in a previous study on older adults, eating alone was reported as a significant risk factor for high PHQ-9 scores, indicative of depression [30,44,48]. This result is consistent with a previous study using the geriatric depression scale (GDS) in the elderly over 65 years of age, which indicated that older adults who ate alone had higher rates of depression than those who ate with others [46].…”
Section: Discussionsupporting
confidence: 90%
“…Several previous studies have reported that eating alone negatively influences health for various reasons without clarifying the reasons behind its increase [18,24,[41][42][43]. Reports suggest that a lack of diverse nutrient and food intake should be associated with increased levels of social isolation, depression, and decreased quality of life [24,44]. This study identified 7037 older adults from the 2016-2020 KNHANES database and examined their health, diet, food and nutrient intakes, depression, and quality of life that depended on the frequency of eating alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in females, the total energy intake (carbohydrate, fat, and protein) was signi cantly different between the MetS and non-MetS groups. This result is supported by a previous study, which reported that the dietary quality and food diversity of females was better than that of males [44]. Moreover, the overall low nutrient intake and low nutrient density of meals were the major nutritional problems in the group of ESH.…”
Section: Discussionsupporting
confidence: 83%